Impact of Hindiya Dam on Rotifera Community of Euphrates River on the Northern of Babil Governorate, Iraq - Al-Bahathy, Idrees A. A.; Nashaat, Muhanned Remzi (Iraqi Journal of Science, 2021)
This study was the first of its kind on the Hindiya Dam, which is considered one of the important dams in Euphrates River. Five sites were chosen on the north of Babil Governorate in order to know the rotifers biodiversity features and the impact of the Hindiya Dam on it’s during the 2019. Site2(S2) was located near the dam to reflect the rotifers diversity of this site, whereas , S1 was located at the upstream of the dam as a control site, and S3, S4 and S5 were located down the dam. Rotifers showed higher density average at Hindiya Dam site compared with sites downstream the dam which was 9164 Ind./m3, whereas density average at the site downstream the dam was 5540 Ind./m3, site (downstream the dam ) decreased clearly compared with the dam site. It was showing the relative abundance index of rotifers: Keratella cochlearis was with the highest percentages followed by Rotaria neplunia, Syncheta oblonga and K. valga at the sites of study area. The study confirmed that the dam reservoir was the source of pelagic rotifers for the outflowing river which led to increase species numbers about 104 species of rotifers. The average values of species richness index of rotifers declined from 1.64 at Hindiya Dam site to 1.58 at site below the dam. Euphrates River rotifers were considered generally from moderate richness to disturbed during 2019 in study area. Site 3(downstream the dam) had the lowest similarity values with site 5 which was 47.5% in rotifers group. Whereas, the highest Jaccard similarity index percentage was between sites 1 with 4 which reached to 76.2%. The Shanon- Weiner index of rotifers reported average values at the dam site 1.7 and 1.8 bit/Ind. at site below the dam. Also, the average values uniformity index of rotifers increased from 0.6 at Hindiya Dam site to 0.7 at site downstream the dam. Euphrates River rotifers were considered generally as little diversified because of index value was ranged from 1 to 2 during 2019 in study area. According to uniformity index values, Euphrates River rotifers were considered generally from unbalanced to moderate balanced in study area. The constant species of rotifers showed that constant species were 8 at the dam site. While, it decreased to 7 constant species at site (downstream the dam). It was concluded that Hindiya Dam had a great effect on the spatial composition of the rotifers community related to the change in the hydrological conditions from current water in site1 to limnetic basins in site 2 (the dam reservoir) then again to current water at site 3, 4 and 5 downstream the dam.